Volume 2: Aircraft Engine; Coal, Biomass and Alternative Fuels; Cycle Innovations 2013
DOI: 10.1115/gt2013-94971
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Mission Analysis for a Regenerated Turboshaft

Abstract: The aim of the study presented in this paper, is to compare helicopters employing simple cycle turboshaft engines, with helicopters employing novel regenerated turboshafts. Two existing helicopter configurations, a Twin Engine Light and a Twin Engine Medium are compared against regenerated configurations. The reference installed engines of both helicopters are notionally optimized by incorporating a heat exchanger, which enables heat transfer between the exhaust gas and the compressor delivery air to the combu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The exhaust gas of a conventional turboshaft carries and dissipates a big amount of heat into the environment [11]. In this module, a PGU is installed after the turboshaft through an evaporator, where part of the exhaust heat will exchange to the organic working fluid and convert into steam under equal pressure (point 2 to 3).…”
Section: Integrated Waste Heat Recovery Module Of Helicoptersmentioning
confidence: 99%
See 1 more Smart Citation
“…The exhaust gas of a conventional turboshaft carries and dissipates a big amount of heat into the environment [11]. In this module, a PGU is installed after the turboshaft through an evaporator, where part of the exhaust heat will exchange to the organic working fluid and convert into steam under equal pressure (point 2 to 3).…”
Section: Integrated Waste Heat Recovery Module Of Helicoptersmentioning
confidence: 99%
“…The exhaust gas of turboshaft engines does not provide power, so it can be used as the heat source of a recuperator, which can preheat compressor discharge air before it enters the combustion chamber [10], [11]. Zhang et al [12] compared the tubular and primary surface recuperators of turboshaft engines by calculating their efficiencies of converting the exhaust heat.…”
Section: Introductionmentioning
confidence: 99%
“…Variable-speed power turbine technology, which can mitigate severe engine power turbine efficiency decrements at reduced RPM, enabling the rotor to slow down and improve rotor propulsive efficiency by 2-3%, continues to be explored (Welch et al, 2012). A recent study employing heat exchangers and regeneration reported a 35% reduction in mission fuel burn and CO 2 is possible, but results in a two to three times increase in NO x (Fakhre et al, 2013).…”
Section: Ongoing Propulsion Research Within Nasamentioning
confidence: 99%